Racial disparities in receipt of radiation and brachytherapy in cervical cancer patients: Do they exist in a SEER-Medicare population? - Emily G. Gleason; Daniel H. Saris; Elizabeth A. Tubridy; Colleen M. Brensinger; Emily M. Ko (Elsevier, 2024)
Objectives: To evaluate if race is associated with disparities in receipt of radiation (RT) and outcomes for Medicare patients with cervical cancer who are candidates for primary radiation-chemotherapy. Methods: This SEER-Medicare retrospective study included White and Black patients with stage IB1 through IVA squamous cell carcinoma or adenocarcinoma diagnosed 2000-2017 who were candidates for primary radiation-chemotherapy. Receipt of treatment by race and associated cancer specific (CSS) and overall survival (OS) outcomes were analyzed using frequency distributions, chi squared, log rank, multivariable Cox proportional-hazards models, and multivariable logistic models. Results: 1038 patients (84.9 % White and 15.1 % Black) were included. 825 (79.5 %) received RT, and 601 (57.9 %) received brachytherapy (BT). Blacks were more likely to undergo RT than Whites (86.0 % vs. 78.3 %, p = 0.028) and had similar rates of BT (58.0 % vs. 57.9 %, p = 0.986). Median RT duration was 64.0 days (IQR 52.0, 75.0), and 276 (33.5 %) completed treatment in ≤ 56 days, with no differences by race (p = 0.488, 0.303, respectively). BT was more frequently provided at larger hospitals, National Cancer Institute-designated cancer centers, and teaching hospitals. When adjusted for covariates, no significant differences in RT, BT, or RT duration by race were identified. Median unadjusted OS was 3.58 years (95 % CI 2.92, 4.42) for White patients and 2.50 years (95 % CI 2.0, 5.25) for Black patients, with no differences in OS (HR 0.93, 95 % CI 0.75, 1.13) or CSS (HR 1.13, 95 %CI 0.86, 1.43). Conclusions: Black Medicare patients with cervical cancer had greater receipt of RT than White patients, similar rates of BT, and no difference in survival.